OP0033 FIBROBLAST GENE, FKBP7 INDUCED BY Ca2+ DEPENDENT ER STRESS ASSOCIATED WITH CLINICAL OUTCOME IN RHEUMATOID ARTHRITIS AND CROHN’S DISEASE; MULTI-CENTRE GWAS AND FUNCTIONAL STUDIES - Maurits, M. P.; Cameron, A.; Jelinsky, S.; Blüml, S.; Abasolo, L.; Askling, J.; Barton, A.; Böhringer, S.; Cope, A.; De, S.; Emery, P.; Eyre, S.; et al. (Annals of the rheumatic diseases, 2024)
Background:Studying which biological pathways are involved in reaching remission in auto-immune diseases could highlight possible targetable mechanisms. Rheumatoid arthritis (RA) is the ideal model disease to study this hypothesis due to well-defined and widely-used measures of disease activity.Objectives:To increase understanding of the mechanisms and biological pathways underlying autoimmune disease remission through GWAS directed functional studies.Methods:The RTCure network collected genetic data of 5,622 deeply phenotyped treatment naive RA patients with longitudinal disease activity data. Data were uniformly QC’ed and imputed using the Haplotype Reference Consortium reference panel. We carried out a GWAS per dataset with DAS28-CRP below 2.6 at 6 months as our outcome, including top 10 principal components, age and sex as covariates. We combined the results using a fixed-effect meta-analysis. SNPs were mapped to genes using Open Targets Genetics. We assessed gene expression using single cell RNAseq of synovial biopsies (AMP-I [1], PEAC [2], Zurich and Queensland) and eQTL data of circulating CD4+ T-cells from untreated RA patients (NEAC) [3]. To investigate the role of Ca2+ induced endoplasmic reticulum (ER) stress on FKBP7, Rheumatoid Arthritis fibroblast-like synoviocytes (RA-FLS) HPRT-knockout cells were stimulated with 400nM thapsigargin (Tg) for 24 hours and cell lysate was collected for RNA analysis. Relative mRNA expression of FKBP7 and stress-related genes CHOP, Grp78 and sXBP1 was calculated against the housekeeper β-actin.Results:Our top hit (P < 5 x 10-8), rs16866400 (Figure 1A-B), has the strongest e-, p- and sQTL association with FK506 binding protein 7 (FKBP7), whose relevance to auto-immunity is understudied. The association was not driven by CCP status, HLA or DMARD usage. The FKBP7 protein is an ER resident chaperone regulating the folding of proteins. Both public and proprietary data show that FKBP7 is differentially overexpressed in a key RA tissue, fibroblast-like synoviocytes (FLS), rather than in circulating B- and T-cells(Figure 1C-E). FKBP7 expression in blood associated both with baseline and change in DAS28-CRP. (Figure 1F) Our studies show that in response to Tg induced Ca2+ ER stress, but not other stressors such as tunicamycin or pro-inflammatory cytokines, FKBP7 was upregulated in RA FLS (Figure 2). FKBP7 has been found to regulate the NOD2 pathway[4]. As this is strongly associated with inflammatory immune responses in Crohn’s Disease (CD), we checked published Crohn’s progression GWAS data for colonic FKPB7 eQTLs.[5] 22% of the colonic FKBP7 eQTLs (GTEx) included in the CD GWAS were significantly (P < 0.05) associated with CD severity.Conclusion:We found the ER resident molecular chaperone encoding gene FKBP7 to link to both RA remission and CD severity. Our functional studies demonstrate a role for the chaperone in the regulation of Ca2+ ER stress and highlights FKBP7 as an interesting gene for further research related to the induction of remission. Elucidating the underlying mechanisms will both increase our understanding of auto-immune pathophysiology as well as facilitate the discovery of novel treatment targets.REFERENCES:[1] Zhang et al, 2019, Nat Imm.[2] Lewis et al, 2019, Cell Rep.[3] Thalayasingam et al, 2018, A&R.[4] Warner et al, 2013, Sci. Signal.[5] Lee, J. C., Biasci, D., et al., 2017, Nat Genet.Figure 1.(A) Manhattan plot, dashed line at p = 5 x 10-8, (B) forest plot of rs16866400 locus, (C) FKBP7 expression in fibroblasts, monocytes, T-cells and B-cells in RA, osteoarthritis and healthy participants [1] (n = 55 RA patients), (D-E) expression across cell types in arthritis patients (n=355 RA patients and n = 26 synovial tissues of 5 arthritides respectively) and (F) association between FKBP7 levels in blood and DAS28-CRP (response).Figure 2.Thapsigargin treated (24h) vs untreated RA-FLS HPRTKO. Relative mRNA expression of (a) FKBP7 and stress genes (b) CHOP, (c) Grp78 and (d) sXBP1 calculated against β-actin. n=8/groupAcknowledgements:We would like to acknowledge support by SPIDeRR Horizon EU (grant 101080711), RTCure, the IMI2 JU (grant 777357), ZonMW (grant 90719069), MRC/Versus Arthritis MATURA Consortium, Versus Arthritis Inflammatory Arthritis Centre Versus Arthritis, NIHR Newcastle Biomedical Research Centre, NIHR Leeds BioMedical Research Centre, UK Medical Research Council (TACERA) and Pfizer.Disclosure of Interests:Marc P. Maurits: None declared, Amy Cameron: None declared, Scott Jelinsky No conflict of interest applies to this abstract, Stephan Blüml: None declared, Lydia Abasolo: None declared, Johan Askling: None declared, Anne Barton: None declared, Stefan Böhringer: None declared, Andrew Cope: None declared, Saurav De No conflict of interest applies to this abstract, Paul Emery: None declared, Stephen Eyre: None declared, Vasanthi Priyadarshini Gaddi: None declared, Isidoro González-Álvaro: None declared, Carl S Goodyear: None declared, Xinli Hu No conflict of interest applies to this abstract, Tom Huizinga: None declared, Martina Johannesson: None declared, Samantha Jurado-Zapata: None declared, Lars Klareskog: None declared, Dennis Lendrem: None declared, Paul Martin: None declared, Iain B. Mc Innes: None declared, Raphael Micheroli: None declared, Ann Morgan: None declared, Fraser Morton: None declared, Najib Naamane: None declared, Yasuo Nagafuchi: None declared, Gisela Orozco: None declared, Leonid Padyukov: None declared, Caron Paterson: None declared, Costantino Pitzalis: None declared, Darren Plant: None declared, Duncan Porter: None declared, Louise Reynard: None declared, Luis Rodriguez Rodriguez: None declared, Daniela Sieghart: None declared, Paul Studenic: None declared, John Taylor: None declared, Rene E.M. Toes: None declared, Erik B. van den Akker: None declared, Annette H.M. van der Helm – van Mil: None declared, Lotta Vaskimo: None declared, Suzanne Verstappen: None declared, Helga Westerlind: None declared, John Isaacs: None declared, Myles Lewis: None declared, Arthur Pratt: None declared, Caroline Ospelt: None declared, Aaron Winkler No conflict of interest applies to this abstract, Ranjeny Thomas: None declared, Rachel Knevel: None declared.